DAMPAK PAWAI OGOH-OGOH TERHADAP SOSIAL BUDAYA MASYARAKAT DI DESA ADAT KUTA - Indah Sista Prabandari; I Wayan Sonder (UHN IGB Sugriwa Denpasar, 2021)
Parade of ogoh-ogoh is one of the cultural art activities of the Bali community which can be used as a tourist attraction. The parade of ogoh-ogoh is a parade which is performed on Pengerupukan Day, a day before Hari Raya Nyepi (Silent Day). One of the villages which perform such a parade every time Silent Day comes is Kuta Customary Village. This study aims at identifying the potentials, the obstructions, the social cultural effects, the perception and attitude of tourists towards the parade of ogoh-ogoh as a tourist attraction.Qualitative method was employed in this study and the data needed were collected by observation, deep interview, and documentation. The informants used in this study were purposively determined. The study is that it positively affects the interpersonal relationship among the community members, it can minimize social deviations, it contributes to the development af arts and tradition, and it can increase the number of tourist visit. The last finding is that the tourists like the parade as a tourist attraction at Kuta Village.Based on the findings above, it can be concluded that the parade of ogoh-ogoh is a potential tourist attraction and positively affects. The suggestions which are given in this study are: (1). an active coordination among the tourist components (the stakeholders) is needed in developing the parade as a tourist attraction and in overcoming the obstacles which are related to promotion, onlookers, traffic, comfortableness and security; (2). socialization of ogoh-ogoh should be made to the youth all over Bali so that the parade, as a tourist attraction, is not prohibited, still exists and is not getting extinct.